Results of estimating promising winter barley varieties and lines - V. F. Khlystunov; A. A. Dontsova; D. P. Dontsov (Зерновое хозяйство России)
The current paper has presented the results of an analysis of promising winter barley lines and varieties developed by the FSBSI “Agricultural Research Center “Donskoy” to select valuable genotypes for breeding programs. The basis for the analysis of the studied samples was the methodology for a comprehensive estimation of breeding results, developed by the researchers from the FSBSI “ARC “Donskoy” and the FSBEI HE DSTU. The study was conducted at the FSBSI “Agricultural Research Center “Donskoy” in 2021–2023. Sowing was carried out in 6-fold repetition, the local variety ‘Timofey’ was taken as a standard. There have been analyzed 14 economically valuable traits, identified as the most significant according to the methodology for a comprehensive estimation of barley breeding identifiers. The purpose of the current study was to conduct a comparative estimation of breeding winter barley lines according to the most significant traits for the selection of promising samples. The studied varieties and lines were ranked according to a set of traits and properties into three groups, such as promising, not very promising, and unpromising. The promising group included the new varieties ‘Step’ and ‘Alabai’, sent to the State study in 2, 5, 6 and 8 regions of the Russian Federation in 2022 and 2023, respectively, as well as the lines ‘Parallelum 2015’, ‘Parallelum 2136’, ‘Pallidum 2100’ and ‘Bezosty 2074’, characterized by high indicators of a complex of basic economically valuable characteristics and properties. These samples are being planned to send to the State Commission of the Russian Federation for Testing and Protection of Breeding Achievements.